Efficacy and safety of PDE5 inhibitors in middle-aged and old patients with and without hypogonadism - Chunlin Wang; Hui Zhang; Fu Wang; Jun Guo; Jianlin Yuan; Guangdong Hou; Ming Gao; Zheng Li; Yan Zhang (The Aging Male, 2024)
Purpose Although several reviews have evaluated the use of PDE5 inhibitors (PDE5i) for treating erectile dysfunction (ED), their specific use in middle-aged and old patients has not been fully evaluated. Given that elderly patients with ED often have a complex combination of systemic and sexual health risk factors, the safety and efficacy of PDE5i in such a context are hereby reviewed.Materials and methods A thorough examination of existing literature has been conducted on PubMed.Results PDE5i has good safety and efficacy, but the situation is more complex for patients with hypogonadism than those with normal testosterone levels, with reduced responsiveness to PDE5i. In this case, combination therapy with testosterone is recommended, safe and effectiveConclusions Eliminating or reducing reversible risk factors and controlling or slowing the development of irreversible factors is an important foundation for using PDE5i to treat ED in all patients, especially middle-aged and elderly ones.